Desoneraç\~oes em alta com rigidez da carga tributária: O que explica o paradoxo do decênio 2005-2014? - Rodrigo Octávio Orair (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper uses Brazilian monthly tax burden time series as an input for a study of its recent dynamic determinants. The estimates shows that tax burden reached 33,4% of GDP in 2014 that is lower than 33,6% of 2005 and without trend of growth. In addition, it presents an analysis of tax policy in Brazil that is characterized by tax cuts predominance. Based on this assumptions the paper is dedicated to a paradox: why is the tax burden growing in the presence of tax cuts during the decade 2005-2014? The causes of this paradox are investigated by a descriptive analysis and an econometric model with variable parameters. The main objectives are: to evaluate different trajectories of taxes by the economic base on which is levied, relations among taxing and economic bases and influences of tax cuts.
Keywords: H20; C32; 330; tax burden; variable parameter model; tax cuts